145k views
2 votes
3x + 2y = A

5x + y = B

Eliminating the variable y from the system of equations results in -7x =

2B - A
A + 2B
A - 2B

User Joseantgv
by
5.0k points

1 Answer

2 votes

Answer:

A - 2B

Explanation:

3x + 2y = A

5x + y = B

The first equation has 2y. The second equation has y.

If you multiply the second equation by 2, it will have 2y.

Then you subtract teh second equation from the first equation.

2y - 2y = 0, so you eliminate the y variable.

********

3x + 2y = A

2(5x + y) = 2B

********

3x + 2y = A

10x + 2y = 2B

********

Subtract the second equation from the first equation.

3x + 2y - (10x + 2y) = A - 2B

3x - 10x + 2y - 2y = A - 2B

-7x = A - 2B

Answer: A - 2B

User Shersha Fn
by
5.1k points